SYSTEMATIC LITERATURE REVIEW EFEKTIFITAS MEDIA PEMBELAJARAN BERBASIS TEKNOLOGI TERHADAP PRESTASI DAN MOTIVASI BELAJAR SISWA SD - Pangestu, Bima; Rasyid, Arif Al; Annam, Muhamad Khoiril; Reza, Ahmad Irvani; Darwanto (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This study aims to analyze the effect of technology-based learning media on the academic achievement and learning motivation of elementary school students through a Systematic Literature Review (SLR) approach. Articles were collected from the Google Scholar database within the period of 2021–2026. The selection process was carried out systematically through the stages of identification, screening, eligibility, and inclusion, resulting in 14 articles that met the inclusion criteria. The findings indicate that technology-based learning media, such as interactive PowerPoint, learning videos, Wordwall, Nearpod, Augmented Reality, Articulate Storyline, educational games, Canva, Google Classroom, and WhatsApp Group, consistently have a positive effect on students’ academic achievement and motivation. Digital media is able to improve conceptual understanding, learning outcomes, interest, enthusiasm, and active engagement of students in learning. The improvement in academic achievement occurs due to the visual and interactive presentation of materials, while the increase in motivation is caused by a more interesting and enjoyable learning atmosphere. Although there are challenges such as limited infrastructure and teachers’ technological skills, the integration of technology-based media still contributes significantly to improving the quality of learning in elementary schools. Therefore, the use of technology-based learning media needs to be continuously encouraged to support the improvement of students’ academic achievement and learning motivation.